Serotype Sensitivity of a Lateral Flow Immunoassay for Cryptococcal Antigen - Gates-Hollingsworth, Marcellene A. (American Society for Microbiology, 2013)
To meet the needs of a global community, an immunoassay for cryptococcal antigen (CrAg) must have high sensitivity for CrAg of all major serotypes. A new immunoassay for CrAg in lateral flow format was evaluated and found to have a high sensitivity for detection of serotypes A, B, C, and D.